(untitled) (Qawanin Jurnal Ilmu Hukum, 2021)
"Juridical Review of Authentic Deeds as Evidence in Civil Cases at the Makassar District Court ". Under consideration (Dr. Hasan Kadir, SH., MH) as Chief Advisor and (Jasmaniar, SH., MH) as Member This study. The purpose of this research is to find out the judge’s assessment of the strength of authentic deed evidence in the civil case examination process in practice at the Karanganyar District Court and judges’ considerations in assessing authentic deeds which are argued for errors, fraud or coercion. This study aims to identify and analyze judges ’judgments regarding the strength of authentic deed evidence in the civil case examination and analyze judges’ considerations in assessing authentic deeds which argue that there are errors, coercion or errors. fraud. The research method used in writing this thesis is an empirical method, with the coverage of secondary and primary data, the research was conducted in a location, namely the Class 1A Makassar District Court. Research Results Based on the description of the results of the research and data analysis, it can be concluded that the strength of the authentic deed evidence will be weak and it can even be canceled if during the examination in court, it turns out that the authentic deeds were made on the basis of errors. There must be evidence at the time the deed is submitted, then in the trial the judge will ask whether there is any pressure (there is an element of imbalance) including fraud and being forced to be under pressure. If in the making of the authentic deed it is proven that the authentic deed was made based on an error, the authentic deed can be canceled.